Kepatuhan Pedagang Pasar Induk Lau Cih Terhadap Kebijakan Protokol Kesehatan dalam Pencegahan Covid-19 di Kecamatan Medan Tuntungan - Sagala, Ridal Rismauly (Universitas Audi Indonesia, 2021)
Lau Cih wholesale market traders' compliance with health protocol policies in preventing COVID-19 in the Medan Tuntungan sub-district tends to be low. Lau Cih's parent market participants' compliance is related to information, monitoring and suppression (punishments and threats). This study aims to analyze the factors that match the compliance of Lau Cih market traders in carrying out health protocols in preventing COVID-19 in the Medan Tuntungan sub-district. The type of research used is survey research using a cross sectional design. The population in this study were all traders at the Lau Cih Main Market, Medan Tuntungan District, Medan City, opening 1,502 people and the research sample as many as 94 people. Data collection with secondary data and analyzed by Chi Square statistical test with 95% confidence level. The results showed that information about COVID-19 and health protocol policies on parent market players in carrying out health protocols in preventing COVID-19 was not good at 70.2%, supervision to control compliance was not good at 69.1%, suppression (punishment) was not good. and threats) on traders with both 70.2% and compliance to comply with major health protocols by non-compliance with 81.9%. The conclusion of this study is that information, supervision and suppression (punishments and threats) are related to the compliance of Lau Cih wholesale market traders in carrying out the COVID-19 prevention health protocol in Medan Tambang District (p-value < 0.05). It is recommended for market managers to further increase routine supervision to increase awareness of traders' compliance in carrying out COVID-19 prevention health protocols and market managers to continue to pay attention to the condition of Lau Cih's wholesaler in compliance with health policies in preventing covid-19 in Medan Tuntungan sub-district